Relationship between glucose homeostatic disorders and testosterone in adult Nigerian women with polycystic ovary syndrome - Amadi, Collins; Green, Kinikanwo I. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Polycystic ovary syndrome (PCOS) is associated with hyperandrogenemia which is hypothesized to induce glucose homeostastic disorders among women with the syndrome. This study was thereby set to investigate the status of glucose homeostatic disorders and their relationship with testosterone among women with PCOS in Port Harcourt, Nigeria. Methods: This was a retrospective study of 224 women with PCOS who had visited a tertiary hospital in Nigeria over a 10-year period. The laboratory characteristics of these patients were evaluated. Records on age, fasting plasma glucose (FPG) and serum total testosterone (TT) were collected and analyzed using Shapiro-Wilk, descriptive, chi-square, Fisher’s exact, two-way analysis of variance, and Pearson’s tests. A p-value <0.05 was considered significant. Results: Glucose homeostatic disorders were documented in 49.1% of the study population. Impaired fasting glucose (IFG) and diabetes mellitus (DM) was observed among 37.5% and 11.6% of the study population respectively. There was difference in the mean TT levels among those with normal FPG, IFG, and DM (P<0.001). Those with DM had higher TT levels (2.47 ± 0.83 nmol/l) than those with IFG (2.12 ± 0.63 nmol/l) and normal glucose homeostatic status (1.63 ± 0.47 nmol/l). TT correlated positively with FPG among the overall study population (r=0.465; p-value = < 0.001), among those with IFG (r = 0.591; p-value=0.004), and among those with DM (r=0.404; p-value =0.012). Conclusions: Glucose homeostatic disorders are common among PCOS patients in our environment, especially among those with higher testosterone levels. This warrants screening of all PCOS patients for glucose disorders as part of their management strategies.